Immobilization of penicillin G acylase on amino functionalized mesoporous silica - Sridevi, N.; Pallavi, Shah; Asmita, Prabhune (Research Journal of Biotechnology, 2008)
Penicillin G acylase was immobilized on Amino functionalized mesoporous silica by adsorption method. In this paper we present the effect of penicillin G acylase immobilization on amino-functionalized mesoporous silica and the effect of silica as host matrix on enzyme kinetics. The loading capacity of immobilized Penicillin G acylase is 34 mg protein per 0.5 g of SBA-15. About 65% of the protein was adsorbed on mesoporous silica. The stability of penicillin acylase was enhanced after immobilization on mesoporous silica. The adsorbed enzyme is more stable than the soluble form, both to temperature and pH environments and retained 73% of its activity.
Keywords: Amino functionalized mesoporous silica; Immobilization; Penicillin G acylase; pH and temperature stabilities

Media optimization for the production of cephalosporin C acylase from a novel bacterial source: alcaligenes xylosoxidans MTCC*491 - Nupura, Hirve; Asmita, Tingare; Sharat, B.; Asmita, Prabhune (Research Journal of Biotechnology, 2008)
The Gram-negative bacterium Alcaligenes xylosoxidans MTCC *491 has been studied for the production of cephalosporin C acylase (CCA), a pharmaceutically important enzyme. The enzyme hydrolyses cephalosporin C (CPC), a natural product, to 7-aminocephalosporanic acid, a key intermediate in the production of semisynthetic cephalosporin antibiotics. Effect of medium, pH, temperature, carbon source, nitrogen source and incubation time, on the production of CCA was studied. 7.7 IU/ml activity was obtained when Luria Bertani broth (LB) was used as a fermentation medium. Glucose and galactose increased the enzyme activity by 9 % and 22 %, while all the nitrogen sources tested showed a repressive effect. Maximum CCA activity was observed around the 5(th) day of incubation indicating potential role of CCA in secondary metabolism. pH 8.0 and 40 degrees C were found to be the optimum conditions for acylase activity.
Keywords: alcaligenes xylosoxidans MTCC*491; cephalosporin C (CPC); cephalosporin C acylase (CCA); fermentation carbon source; nitrogen source

Antibacterial properties of linolenic sophorolipid and its chemically esterified methyl ester form - Reetika, Gupta; Kumar, Uma S.; Asmita, Prabhune (Research Journal of Biotechnology, 2012)
The antibacterial activity of Linolenic SL mixture (containing 80% lactone) and its methyl ester derivative against Gram positive (B. subtilis) and Gram negative (E. coli and P. aeruginosa) bacteria is reported here. Bacterial cultures were treated with increasing concentrations of Linolenic SL mixture and its methyl ester derivative and antibacterial activity was checked at different time-intervals (2, 4 and 6 hrs) using standard dilution micromethod and spread plate method. Decrease in bacterial colonies was observed with increase in concentrations of compounds as well as incubation time but the level of effectiveness varies with the compound and bacteria. The minimum inhibitory concentrations (MIC) of Linolenic SL mixture (LNNSL, containing 80% lactone) against B. subtilis, E. coli and P. aeruginosa were found to be 20, 10 and 10 mu g ml(-1) respectively. The MIC values of methyl ester form (LNNSLME) against B. subtilis, E. coli and P. aeruginosa were determined to be >20, 20 and 20 mu g ml(-1) respectively. The results suggest that Linolenic SL mixture (containing 80% lactone) as compared to its methyl ester derivative showed good antibacterial activity towards both the Gram positive and Gram negative bacteria and were found to be more potent against Gram negative bacteria.
Keywords: antibacterial activity; Bacillus subtilis; Escherichia coli; Linolenic sophorolipid mixture; Minimum inhibitory concentration; Pseudomonas aeruginosa; Sophorolipid methyl ester

Gellan Gum a novel polysaccharide matrix for immobilization of thermo-tolerant yeast cells with invertase activity: factorial design and rheological studies - Sulabha, Karandikar; Asmita, Prabhune (Research Journal of Biotechnology, 2012)
The microbial extracellular polysaccharide gellan gum has been explored for its application in whole cell immobilization. Preliminary evaluation of the physicochemical properties of gellan gum in the presence of monovalent cation tetramethyl ammonium chloride (TMACl) was carried out. Gellan gum immobilized cells demonstrated better rheological properties than gellan gum. Attempts have been made to reveal the evaluation of gellan gum as a matrix to immobilize a thermotolerant yeast Kluyveromyces marxianus NCYC 2675. A 3(2) factorial design was used to study the simultaneous effect of two variables. The effect of the polymer concentration and TMACl concentration on various dependent variables like gelling temperature, mean particle size and enzyme activity of the yeast cells was studied. A statistical model with a significant interaction term was obtained to predict the results. Further, optimized immobilized system was evaluated with significant storage stability at 10 C and enhanced reusability with maximum conversion of > 90 % when crosslinked with glutaraldehyde.
Keywords: Gellan gum; Glutaraldehyde; Immobilization; invertase; Rheology; yeast cells